Ciprofibrate treatment in patients with atherogenic lipoprotein phenotype: effects on HDL quality, LDL susceptibility to oxidation and DNA damage - RASLOVA, K; DOBIASOVA, M; NAGYOVA, A; FABRY, R; RAUCHOVA, H; DUSINSKA, M (European journal of clinical pharmacology, 1998)
This study was conducted to examine a complex effect of ciprofibrate therapy in patients with atherogenic lipoprotein phenotype. Effects of ciprofibrate were studied on HDL subpopulations, HDL ability to esterify cholesterol (FER(HDL)), susceptibility of LDL to oxidation as well as on in vivo oxidative DNA damage in peripheral lymphocytes, measured as strand breaks (SBs) by the comet assay. Ciprofibrate treatment significantly decreased total cholesterol, and triglycerides, and increased HDL-cholesterol. The FER(HDL) showed a significant reduction (29.5+/-7.4 to 23+/-7.5% x h(-1), P=0.0001). The relative concentrations of HDL subclasses did not differ between baseline and after treatment. Ciprofibrate induced a significant increase in LDL oxidation lag time (93+/-7 to 102=11 min, P=0.02) and a decrease in DNA strand breaks (34.0+/-16.2 to 17.8+/-7.5, P=0.02). A significant correlation between maximal rate of diene production and strand breaks was found (r=0.55, P=0.01). These findings may be explained by an improvement of LDL resistance to oxidation, resulting in a decrease in oxidatively modified LDL's cytotoxic effect. Ciprofibrate treatment favourably affected the quality of plasma HDL, probably by the improvement of triglyceride rich lipoprotein metabolism and/or LDL subpopulation profile, increased LDL resistance to oxidation, and decreased the level of DNA damage in peripheral lymphocytes.